Improving audiologic performance with partial insertion of a compressed array despite intracochlear retention of four electrodes during revision cochlear implant surgery: A case report. (January 2015) - Côté, Mathieu; Trudel, Mathieu; Philippon, Daniel; Bussières, Richard
Abstract : Objective and importance: To report a case of partial extraction of the electrode array during revision cochlear implant surgery and to discuss the surgical management of this rare complication. Clinical presentation: The safety of revision cochlear implant surgery has long been demonstrated. Only five cases of partial extraction of the electrode array with intracochlear retention have been reported in the literature. In this report, we describe the case of a 12-year-old boy with post-meningitis deafness who suffered this complication. Intervention: Despite intracochlear retention of four electrodes, the surgical team was able to perform partial insertion of a Med-El compressed array: a total of 8 electrodes out of 12 were implanted in the same scala tympani. Five months after the surgery, the patient had access for the first time to open-set speech recognition. He could recognize 77% of open-set sentences in silence compared to 14% after initial implant activation. Seven months after the surgery, the patient was implanted in his contralateral ear with a Med-El Pulsar split array and now benefits from bilateral auditory stimulation. Conclusion: Partial insertion of a compressed array represents a viable option when facing incomplete extraction of a cochlear implant electrode array. Indeed, our patient's audiologic performance improved significantly and the results seem to surpass those obtained with partial insertion of a conventional electrode array.